Evaluasi Kinerja Operasional Angkutan Lingkungan Bajaj di DKI Jakarta - Fajar, Ibnu (Fakultas Teknik, Universitas Brawijaya, 2014)
Environmental transport bajaj become one of the paratransit modes of public transportation that can only be found in the Jakarta area. The purpose of this research is to determine the operational characteristics, measure user satisfaction levels of operating performance, and develop concepts and strategies for improving the work environmental transport bajaj operations in Jakarta. The statistical test used was Test Validity and Reliability Test by using the method of analysis, namely: the operational characteristics of the transport environment bajaj, Importance Performance Analysis (IPA), and a SWOT analysis. Operational characteristics of the transport environment bajaj driver aspects namely: the number of passengers in a day 28.15 â‰ˆ 28 people / day, duration of operation more than 10 hours (42%), average speed of 52.9 km / h â‰ˆ 53 km / h, operational distance of 8-10 km (48%), and net income of Rp 126,000-Rp driver 150,000 (38%). Meanwhile, from the user aspects: the frequency of use of 7-8 times / week (37%), the waiting time of 5-10 minutes (54%), distance to the activities of <5 km (53%), travel time 5-10 minutes (43 %), and travel costs Rp 10,000-Rp 15,000 (35%). For Importance Performance Analysis (IPA), the level of user satisfaction on the operational performance of the three-wheeler transport environment is satisfactory with an average value of 73.48% suitability level. SWOT analysis can be seen in the value of the weighting factor of 2.5 and the value of the internal strategy of weighting factor of 2.3 so that the external strategy in Internal External Matrix (IE) included in the strategy of cell 5 is Stability Strategy is the strategy adopted without changing the strategic direction that has been set. Thus the concept and strategy to be implemented are not add-wheeler transport modes environment but need to increase the environmental performance of transport operations bajaj in Jakarta. Keywords: Environmental Transport Bajaj, Importance Performance Analysis (IPA), SWOT Analysis